2017
DOI: 10.1186/s13613-017-0295-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of extended-spectrum beta-lactamase-producing Enterobacteriaceae in an intensive care unit with no single rooms

Abstract: Background:The transmission of extended-spectrum beta-lactamase-producing enterobacteriaceae (ESBL) is prevented by additional contact precautions, mainly relying on isolation in a single room and hand hygiene. Contact isolation cannot be achieved in our 12-bed ICU, which has only double rooms. We report the epidemiology of ESBL imported, acquired and transmitted in an ICU with no single rooms. Methods:We prospectively conducted an observational and non-interventional study in a French 12-bed ICU. Inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…The MOSAR investigators confirmed afterwards that the transmissibility of ESBL-E between ICU patients was actually weak, and was even 3 times lower for ESBL-producing E. coli when compared to other ESBL-E (number of secondary cases per index carrier: 0.047 and 0.17, respectively) [17]. These findings corroborate those of several single-center studies based on molecular methods (strain and/or ESBL typing) that reported very low rates of cross-transmission from documented ESBL-E carriers, including in units without single-bed rooms, suggesting other potential sources of acquisition, such as healthcare workers, contaminated environmental reservoirs, or patient transports outside the ICU [18,19].…”
Section: Active Surveillance Cultures and Contact Precautions In The supporting
confidence: 86%
“…The MOSAR investigators confirmed afterwards that the transmissibility of ESBL-E between ICU patients was actually weak, and was even 3 times lower for ESBL-producing E. coli when compared to other ESBL-E (number of secondary cases per index carrier: 0.047 and 0.17, respectively) [17]. These findings corroborate those of several single-center studies based on molecular methods (strain and/or ESBL typing) that reported very low rates of cross-transmission from documented ESBL-E carriers, including in units without single-bed rooms, suggesting other potential sources of acquisition, such as healthcare workers, contaminated environmental reservoirs, or patient transports outside the ICU [18,19].…”
Section: Active Surveillance Cultures and Contact Precautions In The supporting
confidence: 86%
“…Meanwhile, higher prevalence of ESBL producing E. coli was observed in ICU. The rate of ESBLproducing E.coli in ICUs varies greatly in different parts of the globe ranging from 13.2% in France (22) to as high as 61% in India (18). The prevalence of ESBL producing E.coli among the ICUs in Iran ranges from 11.4% (23) to 70.6% (24), whereas the prevalence rate in our study was 65.8%.…”
Section: Discussioncontrasting
confidence: 69%
“…20 Recent studies on colonization in ICU patients show rates varying between 2% 21 and up to 56%, 22 and this large range can be explained by different settings and countries, such as the United States and India, as well as different time frames (2001-2005 and 2016). In our cohort, as in most published studies on ESBL-PE colonization, [22][23][24] 22 of 24 ESBL-PE isolates were E. coli.…”
Section: Discussionmentioning
confidence: 56%